Comprehensive characterization of an oily sludge from a petrol refinery: A step forward for its valorization within the circular economy strategy. (1st May 2021) - Jerez, S.; Ventura, M.; Molina, R.; Pariente, M.I.; Martínez, F.; Melero, J.A.
Abstract: Refinery treatment plants produce large quantities of oily sludge during the petroleum refining processes. The hazardousness associated with the disposal of these wastes, make necessary the development of innovative technologies to handle it adequately, linked to the concepts of circular economy and environmental sustainability. This work provides for the first time a methodology for the deep characterization of this kind of wastes and consequently new insights regarding its valorization. A review of works dealing with the characterization of this type of wastes has been addressed evidencing the complexity and variability of these effluents. The oily sludge under study contains a high concentration of Chemical Oxygen Demand of 196 g COD/L, a Total Kjeldahl Nitrogen of 2.8 g TKN/kg, a phosphorous content as PO4 3− of 7 g/kg, as well as a great presence of heavy metals in a different range of concentrations. This sludge is composed of three different phases: oily, aqueous and solid. The oily and the solid phases present high percentages of carbon content (84 and 26%, respectively), related to the presence of alkanes ranged from n-C9 to n-C44 . Therefore, it could be possible their valorization by the synthesis of catalyst and/or adsorbents. A dark fermentation process could be also proposed for the oily phase to obtain H2 as an alternative energy source. Finally, the aqueous phase contains low carbon and nutrients concentration. A previous thermal pre-treatment applied to the oily sludge might increase nutrient and organic loading in the aqueous phase due to solid destruction, making this aqueous effluent suitable for a further conventional biological treatment. Graphical abstract: Image 1 Highlights: Oily sludge is a complex and variable mixture having three different phases. Oily sludge is composed of a broad of organic and inorganic compounds. Deep characterization of the oily sludge phases is a key step for its valorization. Different innovative approaches have been identified for oily sludge valorization.